Review Of The Execution Of The Decision Of The Lubuklinggau State Court Number 15/Pdt.G/2018/Pn Llg - Randa Alala; Slamet Muljono; Emelia Kontesa (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
In 2018, there was a lawsuit filed by Asbiati and Murisa Binti Nang Agus as the Plaintiffs against PT. Buana Sriwijaya Sejahtera (PT. BSS) as Defendant I, Plantation Cooperation of Tritunggal Jaya as Defendant II, Regent of Musi Rawas Utara as Defendant III, and Village Head of Biaro Lama as Co-Defendant that was submitted to the Lubuklinggau District Court and  had  been decided in  Decision  Number: 15/ Pdt.  G/2018/PN.Llg  In  the  course,  this decision  could  not  be  executed.  This  study discusses  the  reasons  for  the  Lubuklinggau District  Court  Decision  Number  15/Pdt.G/2018/PN.Llg which  has  permanent legal  force (inkracht van gewijsde) cannot be executed, as well as discussing the obstacles to the execution of the Lubuklinggau District Court Decision Number 15/Pdt.G/2018/PNLlg. Execution is the implementation of a Court Decision which has permanent legal force (in kracht van gewijsde) which is carried out forcibly by the District Court where the parties file a lawsuit caused by the losing party in the case rejecting to comply with and to carry out the Court's Decision. The approach used in this study was a normative juridical approach. This study used secondary data obtained from primary and secondary legal materials. The results of this study describe a decision that cannot be executed because there is no argument in the Plaintiffs' lawsuit that places a confiscation of collateral (conservatoir beslaag), and confiscation of execution (excekutorial beslaag) for a decision that has permanent legal force (inkracht van gewijsde), so that the decision does not have executive power. While the obstacles that arise are in the form of the absence of a time limit that serves as a guide for the Head  of  the  Lubuklinggau  District Court  to carry out  and  determine an  execution  of a decision, and the resistance by the executed party who does not want to voluntarily carry out the contents of the judge's decision.